2013
DOI: 10.1080/17480930.2013.830906
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of bauxite refining residue (red mud) as a liner for waste disposal facilities

Abstract: Red mud (RM), a waste arising from the bauxite refining, was studied to assess its suitability as a compacted liner material. The geotechnical and hydraulic conductivity (K) characteristics of the RM, as well as the effect of desiccation, were evaluated. RM has index properties satisfying the requirements to achieve low K. The compaction-permeability studies showed that RM may be compacted to a dense homogeneous mass using a moderate compactive effort, while lowest K (61 Â 10 À7 cm/s) was achieved for RM compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 65 publications
(89 reference statements)
4
16
0
Order By: Relevance
“…activity <0·75). This observation is in agreement with the findings of Rubinos et al (2015). It has been observed that the activity value of RMW is closer to that of calcite and mica (=0·2) minerals and is comparable to that of the muscovite (≈0·25) mineral, but lower than that of the kaolinite (≈0·4) mineral (Mitchell, 1976;Skempton, 1953).…”
Section: Physical Characteristicssupporting
confidence: 82%
See 1 more Smart Citation
“…activity <0·75). This observation is in agreement with the findings of Rubinos et al (2015). It has been observed that the activity value of RMW is closer to that of calcite and mica (=0·2) minerals and is comparable to that of the muscovite (≈0·25) mineral, but lower than that of the kaolinite (≈0·4) mineral (Mitchell, 1976;Skempton, 1953).…”
Section: Physical Characteristicssupporting
confidence: 82%
“…The compression behaviour in increasing order is found as sodium chloride > hydrochloric acid > untreated RMW. Evidently, the values of De for both untreated and treated samples are observed to be appreciably lower than that of conventional soils (Rubinos et al, 2015). Generally, in waste materials, the compression mechanism is controlled by applied stresses and changes in physico-chemical processes (Liu et al, 2006;Sowers, 1973).…”
Section: Consolidation Characteristicsmentioning
confidence: 99%
“…A series of RM specimens were prepared by mixing the pulverised RM with distilled water (24 h of equilibrium) to water contents slightly (*0.5 to 2 %) wet of optimum standard Proctor (w opt = 28.1 %), where compacted RM is at its minimum K (Rubinos et al 2015). Then, the resulting wetted RM mixture was compacted using the standard Proctor (ASTM D698) compaction method, from which undisturbed core specimens of known dry density and water content (Table 2) were obtained and sequentially permeated, firstly with water until steady values of K, then with each corresponding chemical, using a rigid-wall, falling-head, permeameter.…”
Section: Hydraulic Conductivity Testsmentioning
confidence: 99%
“…Due to its geotechnical and adsorptive properties of a wide array of contaminants (Wang et al 2008;Bhatnagar et al 2011), RM has been proposed as a liner material (Kalkan 2006;Ç oruh and Ergun 2010;Rubinos et al 2015). However, the chemical compatibility of RM liners (RMLs) has not been previously studied even though rarely the RML would be exposed merely to water when performing as a hydraulic barrier in actual engineering applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation